Carpal Tunnel Syndrome and Ulnar Nerve Entrapment at the Elbow Are Not Associated With Plasma Levels of Caspase-3, Caspase-8 or HSP27 - Bergsten, Elin; Rydberg, Mattias; Dahlin, Lars B.; Zimmerman, Malin (Frontiers in Neuroscience, 2022)
Background: Nerve compression disorders, such as carpal tunnel syndrome (CTS) and ulnar entrapment at the elbow (UNE), may be associated with apoptosis and neuroprotective mechanisms in the peripheral nerve that may be detected by biomarkers in the blood. The relationships between CTS and UNE and two biomarkers of apoptosis, i.e., caspase-3 and caspase-8, and the neuroprotective factor Heat Shock Protein 27 (HSP27) in plasma were examined in a population-based cohort. Method: The biomarkers caspase-3, caspase-8 and HSP27 were measured in plasma at inclusion of 4284 study participants aged 46 - 68 years in the population-based Malmö Diet and Cancer study (MDCS). End-point retrieval was made from national registers concerning CTS and UNE. Independent t-test was used to examine the association between caspase-3, caspase-8 and HSP27 plasma levels and incidence of CTS and UNE. Cox proportional hazards regression was used to investigate if plasma levels of caspase-3, caspase-8 and HSP27 affected time to diagnosis of CTS or UNE. Results: During the mean follow-up time of 22 years, 189/4284 (4%) participants were diagnosed with CTS and 42/4284 (0.9%) were diagnosed with UNE. No associations were found between incident CTS or UNE and the biomarkers caspase-3, caspase-8 and HSP27 in plasma. Conclusions: The apoptotic biomarkers caspase-3 and caspase-8 and the neuroprotective factor HSP27 in plasma, factors conceivably related to a nerve injury, are not associated with the nerve compression disorders CTS and UNE in a general population.